2009
DOI: 10.1016/j.jmb.2009.07.062
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Cleavage Specificity of the Chymotrypsin-Like Serine Protease (3CLSP/nsp4) of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV)

Abstract: Biogenesis and replication of the porcine reproductive and respiratory syndrome virus (PRRSV) include the crucial step of replicative polyprotein processing by self-encoded proteases. Whole genome bioinformatics analysis suggests that nonstructural protein 4 (nsp4) is a 3C-like serine protease (3CLSP), responsible for most of the nonstructural protein processing. The gene encoding this protease was cloned and expressed in Escherichia coli in order to confirm this prediction. The purified protein was crystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
104
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(109 citation statements)
references
References 59 publications
3
104
0
Order By: Relevance
“…The function of Nsp4 domain III is currently unknown. Analysis of the crystal structure of the Nsp4 crystal indicates the presence of two patches of solvent-exposed hydrophobic residues in domain III, implying possible interactions with other molecules (20), thus reinforcing our observation of the binding of Nsp4 domain III to the B2M promoter.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The function of Nsp4 domain III is currently unknown. Analysis of the crystal structure of the Nsp4 crystal indicates the presence of two patches of solvent-exposed hydrophobic residues in domain III, implying possible interactions with other molecules (20), thus reinforcing our observation of the binding of Nsp4 domain III to the B2M promoter.…”
Section: Discussionsupporting
confidence: 84%
“…The active site of the 3C-like serine protease of Nsp4 is located between domains I and II and harbors a canonical catalytic triad comprising Ser118, His39, and Asp64 (20). In the current study, we observed that domain III of Nsp4 bound to the enhancer PAM element of the porcine B2M promoter and contributed to inhibition of B2M transcription, suggesting that its 3C-like serine protease activity was not involved in this inhibitory activity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The sequence analysis implied TSHSV has a similar domain of replicase polyprotein of Arteriviridae, which is related to virus-coded proteinase [26,27] . RT-PCR and fluorescent quantitative RT-PCR based on the sequences we obtained are highly specific and can be used for molecular detection of this pathogen.…”
Section: Discussionmentioning
confidence: 99%